Surgical management of compound skull fracture with exposed brain matter in a third-world country. Issue 5 (9th May 2019) - Kim, Young; Morris, Mackenzie C; Lee, Tiffany C; Earnest, Ryan E
Abstract: We hereby present a case of a 6-year-old boy with exposed brain matter following traumatic injury from a road traffic accident, in a third-world country with poor healthcare resources. The patient was taken immediately to operating theater where two general surgeons performed an emergent craniotomy and debridement. The patient survived the injury and surgery without neurological deficits or other surgical complications. He was discharged home in good condition.